Panthi Dairy: An Entrepreneurial Venture in Pokhara - Pant, Sushil Kumar (Journal of Nepalese Business Studies, 2007)
No abstract available. Journal of Nepalese Business Studies Vol.2(1) 2005 pp.98-100